Actual problems of particular procedure’ forms using in collective labour disputes: ILO’s standards and international review - Kolosov, I. V.; Колосов, І. В.; Колосов И. В. (Одеса : Гельветика, 2018)
This article devoted to investigation of international standards in field of collective labour disputes’ resolution procedures, regional’ problems and features of their using and furthermore ways of survey in aforesaid area.

Стаття присвячена дослідженню міжнародних стандартів у сфері процедур вирішення колективних трудових спорів, регіональних проблем та особливостей їх застосування й подальшим напрямам вивчення в указаній сфері.

Статья посвящена исследованию международных стандартов в сфере процедур разрешения коллективных трудовых споров, региональных проблем и особенностей их применения и дальнейшим направлениям исследования в указанной сфере
Kolosov I. V. Actual problems of particular procedure’ forms using in collective labour disputes: ILO’s standards and international review / I. V. Kolosov // Актуальні проблеми держави і права : зб. наук. пр. Вип. 80 / редкол.: В. В. Завальнюк (голов. ред.) та ін. – Одеса : Гельветика, 2018. – С. 79-96.
Keywords: procedure; collective labour disputes’ resolution procedures; ILO; process; labour law; процедура; колективні трудові спори; МОП; процес; трудове право; МОП стандарти; ILO standards; процедура; коллективные трудовые споры; МОТ; процесс; трудовое право; МОТ стандарты